Genetic and Epigenetic Alterations in Autism Spectrum Disorder - Oztenekecioglu, Bugsem; Mavis, Merdiye; Osum, Meryem; Kalkan, Rasime (Global Medical Genetics, 2021)
It is extremely important to understand the causes of autism spectrum disorder (ASD) which is a neurodevelopmental disease. Treatment and lifelong support of autism are also important to improve the patient's life quality. In this article, several findings were explained to understand the possible causes of ASD. We draw, outline, and describe ASD and its relation with the epigenetic mechanisms. Here, we discuss, several different factors leading to ASD such as environmental, epigenetic, and genetic factors.
Keywords: genetic; epigenetic; autism spectrum disorder